Ways to improve the efficiency of automatic control systems of pressing current collectors for railway service of high speeds - A. S. GOLUBKOV; O. A. SIDOROV; S. N. SMERDIN (Вестник Научно-исследовательского института железнодорожного транспорта)
One of the limiting factors in increasing train speeds on railway transport is the quality of current collection. With increasing operation speeds, the dynamic loads on the current collector from the rolling stock increase and the aerodynamic impact increases as well, which leads to an increase in the variation of the contact pressure, tearing off the current collector from the contact wire, arcing in contact and increased wear of the contact elements. A promising direction in addressing this issue is the use of automatic control systems, allowing to stabilize the amount of contact pressure. The article discusses the features of modern automatic control systems for pressing current collectors, its main disadvantages are indicated. Authors proposed new automatic control circuit for pressing a current collector, characterized by increased speed. A mathematical model of a current collector equipped with a high-speed automatic pressure control system is described. The results of the calculation of the parameters of the high-speed control system are presented, showing the possibility of its use in order to reduce the spread of the contact pressure of the current collector and improve the quality of the current collection at high speeds. Analysis of the characteristics of the transfer functions of the regulator shows that the application of the PI controller algorithm is effective for stabilizing the contact pressure. Since the rod length of the pneumatic cylinder is limited, the regulator is able to maintain pressure for a limited time, after which the rod must be returned to its original position. The speed of the rod is limited by the characteristics of the actuator (electric motor). These features cause a significant variation in system parameters, such as the time constant and the duration of maintaining a stable depression, depending on the values of the controller coefficients kp and ki, which should be set taking into account the parameters of the current collector, operating conditions and type of contact suspension. For the considered current collector model, the optimal values of the controller coefficients are kp = 1.5 and ki= 1.0. Results of the calculations showed that the use of a rapid regulator based on a pneumatic cylinder in the carriage design reduces the standard deviation of the contact pressure to 37 % at speeds of up to 260 km/h.